Out with the old, in with the new: contrasts involving new features with acoustically salient cues are more likely to be acquired than those that redeploy L1 features - Barrientos, Fernanda (Frontiers in Language Sciences, 2024)
Feature-based approaches to second language (L2) phonology conceptualize the acquisition of new segments as operations that involve either the addition of new phonological features, or the rebundling of existent ones. While the deficit hypothesis assumes that only features that are fully specified in the L1 can be redeployed to the L2 in order to create new segments, it has been shown that features which are completely absent in the L1 can also be learned. This article investigates whether a learning scenario in which features are only partially available (that is, they are present in the L1, but are redundant with other features) is less challenging than learning an entirely new feature, even when the new feature has acoustically salient cues. Since Spanish has a much smaller vowel system /i e a o u/, L2 learners of German with Spanish as L1 need to learn a system with front rounded vowels as well as tense/lax contrasts. We tested L1 Spanish speakers' perception of the German contrasts /i/ ~ /ɪ/ (e.g. Miete/mitte, where [+/-tense] is acquired) and /u/ ~ /y/ (e.g. Spulen/spülen, where L1 feature [+/-round] redeploys to a front vowel). The results showed that experienced L2 learners are more successful when discriminating between sounds in a feature acquisition scenario than in redeployment; however, neither of the nonnative contrasts was easier to perceive than the other in the identification task. The differences in performance between tasks and in the acoustic saliency of the cues by contrast (F2, versus duration and F1) suggests that L2 phonological acquisition is likely to take place at a surface level and favors learning through attunement to auditorily salient acoustic cues over